Peningkatan Ketrampilan Merancang Identitas Visual Pada Produk Umkm Binaan Serabut Nusa Berdaya Kabupaten Semarang-Ungaran (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
A good and strong visual identity is a tool in building a brand because it functions to form an impression that influences consumer perceptions. The longer people are familiar with a particular brand, the more likely they are to have a positive attitude toward that brand. In fact, by changing the visual identity of a product, it can also change or improve the brand image in the community and create an Identity. This is what is meant by the concept of brand loyalty, and vice versa if consumers get a negative stimulus from a visual identity of a brand, the biggest possibility is that consumers cancel the desire to try or make repeat purchases. To represent an identity, a logo and a visual system are needed, so that they are important assets in a company, institution, or product as an identity. This need is needed by various levels of business, including MSMEs. This community service program emphasizes increasing the competence of MSME actors in maximizing the potential for selling business products by strengthening the visual identity of the logo. The implementation of this service involves teaching staff (lecturers) from the Information Systems Study Program, Informatics Engineering and Communication Studies as well as students. This program collaborates with as many as 15 (Fifteen) MSME participants to create an identity design and its application media. In its implementation, the design starts from product analysis and then visual output is made, from illustrations to colors.